PENGARUH KOMPETISI DAN STRATEGI ORGANISASI TERHADAP KINERJA MANAJERIAL DENGAN SISTEM AKUNTANSI MANAJEMEN SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Sektor UKM di Kabupaten Serang) - Maelani, Puspita (Pascasarjana Universitas Sultan Ageng Tirtayas, 2017)
This study aims to examine the influence of competition, organizational strategy, and management accounting system on managerial performance in the SME sector of manufacturing in Serang. The sample in this study is the owner or manager (production, marketing and financial department) who have experience for at least 1 year. The data were obtained by sending questionnaires directly to the respondents, 102 questionnaires distributed to respondents and only 72 returning questionnaires. Data are analyzed using SmartPLS. The results of this study indicate that competition and strategy significantly influence the management accounting system. In addition, competition and management accounting systems have a significant effect on managerial performance. However, strategy has no effect on managerial performance. This study finds that the management accounting system is an intervening variable of the effect of competition and strategy on managerial performance in SMEs.Keywords: Competition, Organizational Strategy, Management Accounting System, Managerial Performance, SME manufacturing, Serang.Â